Chromosomal and molecular abnormalities in a group of Brazilian infertile men with severe oligozoospermia or non-obstructive azoospermia attending an infertility service - Mafra,Fernanda A. (2011)
PURPOSE: To determine the frequency of genetic alterations in a population of Brazilian infertile men with severe oligozoospermia or non-obstructive azoospermia. MATERIALS AND METHODS: Retrospective study of a group of 143 infertile men with severe oligozoospermia or non-obstructive azoospermia from the Andrology Outpatient Clinic of the Human Reproduction Service at the ABC School of Medicine. Of these patients, 100 had severe oligozoospermia, and 43 non-obstructive azoospermia. All patients underwent a genetic study which included karyotype analysis and Y-microdeletion investigation. RESULTS: Genetic abnormalities were found in 18.8% of the studied patients. Chromosomal abnormalities were found in 6.2% of the patients, being more prevalent in the azoospermia group (11.6%) than in the oligozoospermia group (4%). Chromosomal variants were found in 8.3%, and Y-chromosome microdeletions in 4.2% of patients. CONCLUSION: The high frequency of genetic alterations (18.8%) in our series justified performing a genetic investigation in a population with idiopathic infertility, as results may help determine the prognosis, as well as the choice of an assisted reproduction technique. Moreover, a genetic investigation could minimize the risk of transmitting genetic abnormalities to future generations such as genetic male infertility, mental retardation, genital ambiguity and/or birth defects.